The Influence of Price, Quality and Model on Clothing Sales Levels with E-Commerce Media - Syah Putra, Arman; Amandin, Amandin; Fauziyah Lamaya, Fauziyah Lamaya; Resista Vikaliana, Resista Vikaliana; Nurul Aisyah, Nurul Aisyah (CV. Inara, 2021)
The background of this research will find out how the price, quality and model can affect the level of clothing sales using e-commerce media using predetermined variables, it will be known whether these variables can affect sales levels using e-commerce media. The method used in this study is to use quantitative methods which will use survey tools and SPSS software to process data. After the data is obtained through surveys, the data will be processed through SPSS software so that it can produce accurate and measurable data. There are several studies related to increasing sales. Therefore, with the existing research base, variables that can affect sales levels will be developed because these variables can be used as a basis for research and developed to improve sales levels. In this study will produce a data that can find out what variables can affect the level of sales, especially with e-commerce media. e-commerce media is a media that is on the rise because during the pandemic, sellers and buyers cannot meet in person due to distance restrictions due to that with the pandemic, many marketplaces have sprung up so that e-commerce media is the right medium at this time.